Redundancy within hospital‐related harm prediction tools. Issue 9 (19th September 2021) - Moran, Chris; Bingham, Gordon; Tuck, Michelle; Crabtree, Amelia
Abstract: The predictive ability and efficiency of inpatient harm screening tools is unclear. We performed a retrospective analysis of approximately 25 000 people admitted to our hospital in 2019. We found that the discriminatory ability of the harm screening tools was at best moderate and could be attributed to one or two questions that overlapped with each other in the harm they predicted.